Elevated serum levels of galectin-3 binding protein are associated with insulin resistance in non-diabetic women after menopause - Yun Chen; Sayantana Das; Guangchao Zhuo; Hong Cai (Elsevier, 2020)
Objective: Galectin-3 binding protein (Gal-3BP) is one of the major fucosylated glycoprotein family members and has recently been implicated in non-alcoholic fatty liver disease, hyperlipaemia and coronary artery disease. Here, we analysed the serum concentrations of Gal-3BP in menopausal women to evaluate the association of circulating Gal-3BP and insulin resistance in females after menopause. Materials and methods: We evaluated serum levels of Gal-3BP in sixty-two non-diabetic women with menopausal status for at least one year. The clinical features, biochemical profiles and homeostasis model assessment of insulin resistance (HOMA-IR) indices were obtained routinely. Results: Gal-3BP levels increased in women with higher HOMA-IR indices and were positively correlated with HOMA-IR indices. The Gal-3BP level was also an independent risk factor for a high HOMA-IR index and showed the most influence on the HOMA-IR index compared to fasting plasma glucose, triglyceride, age and body mass index. The cut-off value of the serum Gal-3BP level was 2234.32 ng/ml, with areas under the ROC curve (AUCs) of 0.68 (HOMA-IR index 1.5), 0.81 (HOMA-IR index 2.0) and 0.93 (HOMA-IR index 2.5). Conclusion: Serum levels of Gal-3BP are associated with impaired insulin sensitivity in non-diabetic menopausal women.